Documentation at the Ethnographic Museum in Zagreb - Vlatković, Aleksandra (2019)
The paper provides a concise overview of documentation management activity per- formed at the Ethnographic Museum in Zagreb during the period ranging from 1919 to this day. It strives to highlight the importance, as well as the changes and the expan- sion of the role of documentation management in museums over time. The continuity of documentation management at the Ethnographic Museum has been pointed out over the first 100 years of its activity and the work of the people who have played a crucial role in the formation and the documentation management at the Museum has been concisely presented. The conclusion presents the current challenges and efforts to harmonise the documentation management tradition with the changes in laws, technological development and international standards.
Bibliografske bilješke uz tekst ; bibliografija i izvori: str. 85-86.
Summary.
Keywords: Muzeji -- Muzejska dokumentacija -- Fundus muzeja -- Inventarizacija građe; Etnografski muzej Zagreb